Assessing Professionalism among First Year Medical Students through Professionalism Assessment Tool - Nabiha Farasat Khan; Muhammad Saeed; Ruksana Majid (University of Lahore, 2024)
Objective: To assess the professional level among 1st year MBBS students of Bolan Medical College, Quetta. Methodology: A descriptive cross-sectional study was carried at Bolan Medical College Quetta from September to November, 2022. All 200 medical stu- dents of 1st year MBBS were invited to participate in the study. A validated Professional Assessment Tool (PAT) was distributed by 3 senior demonstrators during lectures. The PAT contained 33 items within five domains: (1) Reliability and Responsibility, (2) Life-long Learning and Adaptability, (3) Relationships with Others (4) Upholding Principles of Integrity and Respect, and (5) Citizenship and Professional Engagement. Results were prepared by using SPSS version 29. Frequencies and percentages were calculated. A p-value<0.05 was considered as significant. Results: Twenty four out of 200 students were consistently absent at the time of data collection (99% response rate). Fifty one percent were females (n=102/200). Seventy out of 200 students (35%) were 20 years of age. Thirty four percent (68/200) demonstrated only the basic level of critical thinking and only 10 students (5%) demonstrated the higher cognitive level. Overall, statistically significant results were observed at items number 3 and 1 (p-<.001) of domain 3 and 4 respectively (empathizing to the situations of others and actively and productively participating in the profession respectively) Conclusion: Students of 1st year MBBS demonstrate positive attitude towards professionalism.